Strategi STEAM (Science, Technology, Engineering, Art, And Mathematics) dan Dampaknya terhadap Literasi Sains Materi Ekosistem Peserta Didik Kelas V SDN 44 Pontianak Barat - Qonita, Azka Millati; Mansur, Mansur; Setyaningrum, Vidya (PendIPA Journal of Science Education, 2025)
This study aimed to describe the effect of applying the Science, Technology, Engineering, Art, and Mathematics (STEAM) strategy on students’ science literacy in the ecosystem material of grade V at SDN 44 Pontianak Barat. The research employed a quantitative approach with a quasi-experimental design type pretest-posttest control group design. The sample consisted of 52 students selected using a random sampling technique. Data were collected through observation, tests, and documentation, and analyzed using instrument analysis, prerequisite tests, hypothesis testing, and effect size measurement. The results showed that the average science literacy score in the control class increased from 42.08 (low) to 57.09 (moderate), while in the experimental class it increased from 49.02 (low) to 83.23 (high). Hypothesis testing obtained a significance value of 0.001 < 0.05, indicating a significant difference between the use of STEAM and conventional strategies. The effect size of Cohen’s d was 1.055 > 0.8, which falls into the large effect category. Thus, the application of the STEAM strategy has a positive and significant effect on improving elementary school students’ science literacy.